Strategi Pendidikan SMA Darul Ma’arif dan Peran Pemerintah dalam Menghadapi Krisis Literasi Nasional - Muniratri Rachmita; Elisabeth Hana G.S; Qonita Mutmainah; Sabina Namira Rachman; Subakdi Subakdi; Kayus Kayowuan Lewoleba; Abdul Halim; Andreas Bramantyo (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The national literacy crisis is a serious challenge for the education system in Indonesia. This research examines the educational strategies implemented at Darul Ma’arif High School in an effort to improve student literacy and analyzes the role of the government in supporting the improvement of literacy quality at the secondary school level. This research uses a qualitative approach with in-depth interview and observation methods to understand the learning strategies, infrastructure, and literacy programs implemented at Darul Ma’arif High School and through a community service approach in the form of socialization themed "Exploring Your Future, What Major Are You Interested in?". It was carried out as an effort to arouse students' interest in literacy for their awareness in choosing majors. Through a survey in the form of a form, it is expected to measure students' understanding and response to the material presented to be an indicator of their absorption of literacy. The results show that collaboration between schools and government is needed to create a learning environment conducive to improving literacy. This joint effort includes providing supporting facilities, training teachers and developing a relevant curriculum. The findings are expected to provide input for stakeholders in designing strategies to deal with the national literacy crisis.